2013
DOI: 10.1016/j.aap.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Extracting decision rules from police accident reports through decision trees

Abstract: Given the current number of road accidents, the aim of many road safety analysts is to identify the main factors that contribute to crash severity. To pinpoint those factors, this paper shows an application that applies some of the methods most commonly used to build Decision Trees (DTs), which have not been applied to the Road Safety field before. An analysis of accidents on rural highways in the province of Granada (Spain) between 2003 and 2009 (both inclusive) showed that the methods used to build DTs ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 26 publications
1
72
0
Order By: Relevance
“…DTs, and more specifically the Classification and Regression Tree (CART) methods, are frequently applied in the field of safety analysis (Kuhnert et al, 2000;Karlaftis and Golias, 2002;Park and Saccomanno, 2005;Chang and Wang, 2006;Harb et al, 2009;Kashani and Mohaymany, 2011;De Oña et al, 2012;Montella et al, 2012;Abellán et al, 2013;De Oña et al, 2013). A main advantage of DTs is that their structure permits the extraction of Decision Rules (DRs) of the type "if-then".…”
Section: Introductionmentioning
confidence: 99%
“…DTs, and more specifically the Classification and Regression Tree (CART) methods, are frequently applied in the field of safety analysis (Kuhnert et al, 2000;Karlaftis and Golias, 2002;Park and Saccomanno, 2005;Chang and Wang, 2006;Harb et al, 2009;Kashani and Mohaymany, 2011;De Oña et al, 2012;Montella et al, 2012;Abellán et al, 2013;De Oña et al, 2013). A main advantage of DTs is that their structure permits the extraction of Decision Rules (DRs) of the type "if-then".…”
Section: Introductionmentioning
confidence: 99%
“…Pande and Abdel-Aty [9] concluded that there is a significant correlation between lack of illumination and high crash severity. de Oña et al [10,11] pointed out that fatal accidents are associated with roadways with no lighting. Wanvik [12] found that good road lighting can decrease road accidents by one-half based upon a study of 763,000 injury accidents and 3.3 million property-damage accidents in Norway.…”
Section: Effects Of Light Condition On Crashesmentioning
confidence: 99%
“…Juan de ona et al [7] discusses road accidents, analysts many road safety is to identify the main factors that give to crash severity. They applied decision tree approach in the road safety field.…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%